Supporting ontology development with visual modeling tools - Dudáš, Marek; Svátek, Vojtěch, 1967 prosinec 1.-; Řepa, Václav, 1958-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
The current common approach for ontology engineers, that create ontologies and vocabularies in the OWL language for the Semantic Web, and dataset creators, that use these ontologies and vocabularies to annotate data, creating datasets in RDF format, is to work with ontologies directly in their "source" OWL representation. This thesis explores the idea of providing both ontology engineers and dataset creators with visual modeling interfaces that abstract from some OWL complexity, possibly making their work easier and less error-prone. A framework of tools is experimentally developed to test the idea, building on techniques gathered in a comprehensive survey of OWL visualization tools. The framework is based on the exploitation of PURO language for ontological background models (OBM). OBM serves as an initial model of an example situation, from which an OWL ontology seed is generated automatically. The seed is then finalized using any common OWL ontology editor. The creation of an OBM at the beginning of ontology development should allow to clearly define the concepts that are to be covered by the ontology in a simplified way, before the engineer delves into OWL complexity. It also allows choosing OWL encoding style of the generated ontology. Finally, it supports ontology reuse, by enabling automated search for relevant ontologies and reuse of selected entities in the generated ontology. For analysis of ontology suitability for reuse, an ontology usage visualization tool was designed. It is based on summarization of existing datasets, in which the ontology is used, and can also serve as a standalone tool for dataset creators. Parts of the framework were evaluated with users, showing some promising results.
Vedoucí práce: Vojtěch Svátek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor disert. práce]; disertace; dissertations